The Helping by Clicking Types Questionnaire (HCTQ): The Development of a Measure to Assess Different Patterns of Helping by Clicking - Agata Błachnio; Aneta Przepiórka; Paweł Kot; Andrzej Cudo; Małgorzata Sobol (Europe's Journal of Psychology, 2024)
Recently, there has been an increase in the number of aid campaigns launched via social media. The paper explores the phenomenon called “helping by clicking,” which consists in clicking “Like” to support a charitable campaign or cause. The main aim of the paper is to present a new measure: The Helping by Clicking Types Questionnaire (HCTQ), assessing the patterns of helping by clicking. In developing the questionnaire, we relied on the theory of reciprocal altruism. The study included two samples of n = 349 and n = 1,006 participants. The HTCQ consists of 19 items making up three subscales: People, Environment, and Animals. The present research included two independent studies. Study 1 was conducted to determine the psychometric properties of the questionnaire, while Study 2 was conducted to verify the previous results and to test the usefulness of the questionnaire in distinguishing individuals with different patterns of helping by clicking. The measure was designed to assess three aspects of helping: helping people, helping the environment, and helping animals via social media. The study showed that the HCTQ was suitable for measuring patterns of helping by clicking. All HCTQ factors had good Cronbach’s alpha reliability coefficients. The HCTQ concerns a new and largely unexplored area of helping that involves the use of modern technologies. It reveals people’s motivations for helping.